The Existence of Women Clove Climbers in the Household Economy in Bone Regency - Satriani S; Andi Sadriani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to find out:1) The role of women in clove harvesting activities in Pattiro Riolo Village, Sibulue District, Bone Regency, and 2) Social, cultural and economic challenges faced by women clove climbers in Pattiro Riolo Village, Sibulue District, Bone Regency. This type of research uses a case study approach. The number of informants in this study was 10 people who were selected through purposive sampling with informant criteria, namely village heads and women involved in clove climbing work in Paattiro Riolo Village. Data obtained through observation, interviews, and documentation. The validity of the data is used, namely source triangulation, data analysis techniques, namely data condensation, data presentation and conclusion drawn. The results of the study showed that: 1) The role of women in clove harvesting activities in Pattiro Riolo Village, Sibulue District, Bone Regency, namely a) Family economic contribution, b) Women's productive role, and c) Logistical and domestic support, and 2) The social, cultural and economic challenges faced by women clove climbers in Pattiro Riolo Village, Sibulue District, Bone Regency are: a) The views of the surrounding community, b) Malebbi women, d) Wage income.